ANALISIS LATAR CERITA DALAM NOVEL ARAH LANGKAH KARYA FIERSA BESARI - Sujoko Sujoko; Eflin Alkautsar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the setting of the place, time setting and social setting in Fiersa Besari's Novel Arah Langkah. This research is included in the type of qualitative descriptive research. The data used as the object of study is in the form of sentences, phrase clauses and words that refer to the setting of the place, time setting and social setting contained in the novel Arah Langkah by Fiersa Besari. To analyze the data, the author uses the theory of structural approaches. The results of this study can be described by the author that the novel Arah Langkah by Fiersa Besari contains a setting that includes the setting of the place, among others, contained in the expression 1). “Aku tiba di terminal Leuwi Panjang. 2). Time setting can be seen from the expression “Kami baru tiba pukul enam sore sudah cukup gelap”. 3). The social setting is found in the phrase “Seorang anak kecil melempar wadah mi ke laut”. Based on the results of background research, it can be concluded that the setting of the place is more found while the least background is the social setting.